Who Benefits More from the College Expansion Policy? Evidence from China. (February 2021) - Wang, Yapeng
Highlights: Socioeconomically advantaged benefit more from college expansion in China. Different regions of China display different inequality patterns after expansion. Inequality patterns after expansion vary across different types of colleges. The study utilizes Comparative Interrupted Time Series method. Abstract: This study extends the current literature on the relationship between educational expansion and social inequality by examining how the higher education expansion policy in China changed patterns of inequality across the country and within specific geographic regions. Results based on the Comparative Interrupted Time Series analyses indicate that although all individuals benefit from expansion in both overall and academic college enrollment, individuals from advantaged family backgrounds experience greater benefits. This is the case especially for middle and western regions of China. In the eastern region, inequality in overall college enrollment persists after expansion but that in academic college enrollment increases. These findings have implications for understanding the effects of expansion policies and whether they can reduce social inequality.